Irassyaimase as an Unreplyable Utterance in Japanese: Analysis of Ostensible Hospitality - Nishijima, Yoshinori (Intercultural Communication Studies, 2026)
Irassyaimase as an Unreplyable Utterance in Japanese: Analysis of Ostensible Hospitality